Melatih Kemandirian Anak Down Syndrome Dengan Mototrain - Machmudah; Mochammad Shodiq (Universitas Nahdlatul Ulama Surabaya, 2020)
Practicing toilet training from parents to children is quite challenging especially if the child has special needs. For children with Down syndrome, the habit of toilet training takes longer than normal children who can be completed before school age. The purpose of this study was to determine the effectiveness of Mototrain on maternal knowledge and independence of toilet training in children with Down syndrome. Mototrain is an acronym for Module of Toilet Training. The population and sample in this study were parents and students with Down syndrome who had not yet completed their toilet training independence, namely 31 students spread across Grade 1, Grade 2, Grade 3, Grade 4 and Grade 5 in SD C Alpha Kumara. The research design was